An Interesting Presentation of Severe Bicytopenia in A Case of SLE - Manikandan, M Aswin; Josephine, A; Srivastava, Vindu; Lilly, S Mary (Annals of Pathology and Laboratory Medicine, 2021)
We present a case of 25-year-old female who was brought to the hospital for complaints of generalised weakness, fever, and history of melena and haematuria. Following admission complete blood count and peripheral smear was asked; Complete blood count (CBC) findings were haemoglobin 4.2 gm/dl, total WBC count was 14,990, platelet count 7000, reticulocyte count 4%, NRBCs were 15/100 WBCs. Peripheral Smear showed fragmented RBCs, polychromatophils microspherocytes and multiple foci of autoagglutination suggestive of autoimmune haemolytic anaemia. Pertaining to these findings immune workup was done for this patient; coombs test was negative for this patient, but ANA was positive. This identification proved valuable to the patient as; administration of corticosteroids helped to prevent haemolytic transfusion reactions and improved the patient’s haemoglobin and platelet count.